5,7,3′,4′,5′-pentamethoxyflavone (PMF) exhibits anti-obesity and neuroprotective effects in an obese zebrafish model - Muhammad Sufyan, Vohra; Bilal, Ahmad; Emerald R., Taylor; Khaled, Benchoula; Isabel Lim, Fong; Ishwar S., Parhar; Satoshi, Ogawa; Christopher J., Serpell; Eng, Hwa Wong (Elsevier B.V., 2025)
Obesity is a multi-chronic illness characterized by superfluous fat accumulation, contributing to significant metabolic and neurological complications. Current therapeutic approaches have limited efficacy and notable side effects, underscoring an urgent demand for novel, safer alternatives. This study is the first to investigate the anti-obesity potential of 5,7,3′,4′,5′-pentamethoxyflavone (PMF) in vivo using a zebrafish model. Our findings demonstrate that PMF administration exerts pronounced anti-obesogenic effects, evidenced by reductions in blood glucose, plasma triglycerides, total cholesterol, hepatic low-density lipoproteins (LDL), and high-density lipoproteins (HDL). Mechanistically, PMF suppressed hepatic adipogenic and lipogenic gene expression while promoting lipid catabolism through activation of peroxisome proliferator-activated receptor-alpha (PPAR-α) and its downstream enzymes, including acyl-CoA oxidase 1 (ACOX1), medium-chain acyl-CoA dehydrogenase (ACADM), and carnitine palmitoyl transferase 1B (CPT-1β). Additionally, PMF markedly mitigated oxidative stress by lowering malondialdehyde (MDA) and nitric oxide (NO) levels, accompanied by increased antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and glutathione S-transferase (GST). Notably, PMF effectively prevented obesity by suppressing food intake, down-regulating orexigenic genes, and enhancing anorexigenic signals. Furthermore, PMF exhibited neuroprotective properties by elevating brain-derived neurotrophic factor (BDNF) and its receptor tropomyosin receptor kinase B2 (TrkB2), revealing a novel link between metabolic and neurological regulation. This study provides pioneering, comprehensive in vivo evidence supporting PMF as a promising therapeutic candidate with dual beneficial roles in metabolic health and neuroprotection.